Education and job mismatch measuring over-education in the Philippine labor market during fast economic growth years - De Castro, Gregory Silver S.; Evardone, Benju M. (School of Economics, University of the Philippines Diliman, 2018)
This paper aims to analyze the incidence of over_education in the Philippines in 2012 and 2015, which are years when the country experienced relatively fast economic growth. The research employs the use of the method proposed by Epetia (2018) which will be discussed in depth in the later chapters of this paper. The paper by Epetia (2018) studies the incidence of over_education in the Philippines in 2003 and 2009, which were slow economic growth years of the country. This paper aims to extend the analysis by determining the incidence of overeducation in fast economic growth years in 2012 and 2015. The research found that 13,918 out of 79,446 individuals are over_educated. This amounts to 17.52 percent of the sample, and is lower than the level of over_education during 2003 and 2009 as determined by Epetia (2018).